2000
DOI: 10.1046/j.1365-2435.2000.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations in hectare‐scale net CO2 flux, respiration and gross primary production of Arctic tundra ecosystems

Abstract: Summary1. Eddy covariance was used to measure the net CO 2 flux of Alaskan moist-tussock and wet-sedge tundra ecosystems between 1 June and 31 August 1995. The sites were located within 2·5 km of each other and, depending on wind speed and thermal stability, the eddy-covariance measurements integrated surface fluxes over 0·8-26·5 ha (mean 3·8 ha) at the moist-tussock site and 0·1-4·2 ha (mean 0·6) at the wet-sedge site. 2. Both sites were net sinks for atmospheric CO 2 during the 92-day measurement period but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 56 publications
4
48
5
Order By: Relevance
“…The soils at wet sedge tundra sites for which much higher gross photosynthesis was reported in the literature compared to this study (see above) are considered less nutrient-limited than the soils of the investigation site of this study as they were situated at the bottom of mountain valleys (Vourlites et al, 2000;Laurila et al, 2001) or on fine-grained marine sediments at coastal tundra Harazono et al, 2003). On moist tundra sites, e.g.…”
Section: Comparison With Other Tundra Sitesmentioning
confidence: 69%
See 1 more Smart Citation
“…The soils at wet sedge tundra sites for which much higher gross photosynthesis was reported in the literature compared to this study (see above) are considered less nutrient-limited than the soils of the investigation site of this study as they were situated at the bottom of mountain valleys (Vourlites et al, 2000;Laurila et al, 2001) or on fine-grained marine sediments at coastal tundra Harazono et al, 2003). On moist tundra sites, e.g.…”
Section: Comparison With Other Tundra Sitesmentioning
confidence: 69%
“…It amounted to 60% of average R eco observed at a moist to wet tussock tundra at the Kolyma River lowlands in North-East Siberia (Corradi et al, 2005), to 60% of R eco at moist to wet tundra on the Chukotskiy Peninsula (Zamolodchikov et al, 2003), to 47-54% of R eco at a high arctic fen (Soegaard and Nordstroem, 1999;Nordstroem et al, 2001), to 38-44% of R eco at tussock tundra at an Alaskan mountain valley (Vourlites and Oechel, 1999;Vourlites et al, 2000) and to 50% of the average R eco modelled for the whole Russian tundra area (Zamolodchikov and Karelin, 2001). On the other hand, R eco observed in this study was equal to R eco at wet sedge tundra at an Alaskan mountain valley (Vourlites et al, 2000), about two times higher than R eco reported for flooded wet sedge tundra at the coastal plain of Alaska (Harazono et al, 2003) and about 2.3 times higher than R eco at an high-arctic semi-desert at Svalbard (Lloyd, 2001a).…”
Section: Ecosystem Respiration 421 Comparison With Other Tundra Sitesmentioning
confidence: 99%
“…In an analogous study in an Alaskan tundra ecosystem, Oechel et al (2000) found that the ecosystem initially changed from a CO 2 sink to a source due to warming and drying, but that CO 2 emissions decreased and eventually became negative during summers over a 40-year period. Several studies of CO 2 fluxes at wetlands have also indicated the importance of vegetation, both stand age for forested wetlands (Ball et al, 2007) and dominant plant community among different wetland types (Humphreys et al, 2006;Glenn et al, 2006;Vourlitis et al, 2000;Waddington et al, 1998). Understanding the impact of dominant plant communities on an ecosystem's response to changing climatic and hydrological conditions will be important for complete understanding of this issue.…”
Section: Discussionmentioning
confidence: 99%
“…If the effect of decomposition were to increase nutrient availability, there may be an additional uptake of CO 2 owing to higher rates of photosynthesis (Shaver & Chapin 1986;Shaver et al 1998;Johnson et al 2000), although as sink strength in vascular plants decreases, productivity may be offset by substrate-controlled or nutrient-limited CO 2 loss from soil respiration by microorganisms (Nadelhoffer et al 1991;Hobbie 1996;Jonasson et al 1999). Larger sinks of CO 2 are accordingly associated with lower respiration rates in wetter habitats (Vourtilis et al 2000), while short-term experiments designed to explain the net effect of climate warming on soil moisture and the C-balance of tundra plots (Johnson et al 1996) support observational data demonstrating that a shift from net C-input to C-output accompanies the recent drying of tundra habitats (Oechel et al 1993Weller et al 1995).…”
Section:      mentioning
confidence: 99%